Atiyah's introduction to the law of contract/by P. S. Atiyah and Stephen A. Smith - Atiyah, P. S. (Oxford, 2005)
This is the new sixth edition of Atiyah's Introduction to the Law of Contract that offers a clear and comprehensive account of this area of law.
Keywords: Law of contract